2014
DOI: 10.1074/jbc.m113.541490
|View full text |Cite
|
Sign up to set email alerts
|

HERC2 Targets the Iron Regulator FBXL5 for Degradation and Modulates Iron Metabolism

Abstract: Background: FBXL5, the F-box protein subunit of an SCF-type ubiquitin-ligase complex, is a regulator of mammalian iron homeostasis. Results: The HECT-type E3 ligase HERC2 binds to FBXL5 and regulates its stability. Conclusion: HERC2 controls iron metabolism by promoting ubiquitin-dependent degradation of FBXL5. Significance: Our results provide new mechanistic insight into the proteolytic control of iron metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Ubiquitination of IRP2 in high iron is dependent upon an E3 ubiquitin ligase complex containing the F-box protein FBXL5 (F-box and leucine-rich repeat protein 5) [151, 152]. In low iron, FBXL5 is targeted for degradation by the large HECT-type ubiquitin ligase HERC2 [153]. However, when iron levels are high, iron binds to a hemerythrin domain within FBXL5 resulting in its stabilization [154].…”
Section: Post-transcriptional Control Mechanisms - Mrna Degradationmentioning
confidence: 99%
“…Ubiquitination of IRP2 in high iron is dependent upon an E3 ubiquitin ligase complex containing the F-box protein FBXL5 (F-box and leucine-rich repeat protein 5) [151, 152]. In low iron, FBXL5 is targeted for degradation by the large HECT-type ubiquitin ligase HERC2 [153]. However, when iron levels are high, iron binds to a hemerythrin domain within FBXL5 resulting in its stabilization [154].…”
Section: Post-transcriptional Control Mechanisms - Mrna Degradationmentioning
confidence: 99%
“…69 The mechanism linking IR with hemerythrin-dependent destabilization of Fbxl5 is still unknown, but it is likely that IR might indirectly reduce the iron levels required for hemerythrin stability 100 or modulate the levels of the ubiquitin ligase that targets Fbxl5. 101 Moreover, Fbxl5 is also downregulated by hypoxia 97 which can also contribute to the Snail1 stabilization observed in these conditions.…”
Section: Scf-fbxl5mentioning
confidence: 99%
“…FBXL5 is an E3 ubiquitin ligase that target many proteins to regulate their phosphorylation-dependent protein ubiquitination and subsequent degradtion [23,24,25,26,27,28,29,30]. Recently, we reported that FBXL5 mediates the ubiquitination and degradation of cortactin, which is necessary for the invasion and metastasis of GC cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…FBXL5 is an F-box protein, a member of the F-box protein family characterized by the F-box motif comprised of about 40 amino acids [23,24,25,26,27,28,29,30]. The F-box proteins are major components of ubiquitin protein ligase complex SKP1-cullin-F-box (SCFs), which plays a critical role in phosphorylation-dependent protein ubiquitination [23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation